2015
DOI: 10.1136/bcr-2014-206919
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and ABCB4 gene mutation: risk of recurrent cholelithiasis

Abstract: Cholelithiasis is a common problem in the Western world. Recurrent gallstones after cholecystectomy, however, are rare. We describe a case of a young woman with recurrent gallstones after a laparoscopic cholecystectomy leading to cholangitis during pregnancy. Additional testing revealed an ATP-binding cassette B4 (ABCB4) gene mutation. ABCB4 gene mutations leading to a multidrug resistance (MDR)3-P-glycoprotein deficiency are related to, among other diseases, recurrent cholelithiasis. Medical treatment consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…The plasma of the hepatocytes around the nodules appearing as an air halo, copper particle deposition, and positive CK7 expression of intermediate liver cells are morphological characteristics indicative of biliary cirrhosis, and all patients had these findings. In previous research, these findings have been reported to be consistent with histological changes in the liver of adult patients with PFIC3 ( 20 ). Furthermore, liver biopsies revealed ductular proliferation with mild inflammation, which is indicative of early stages of fibrosis in the portal tract.…”
Section: Discussionsupporting
confidence: 87%
“…The plasma of the hepatocytes around the nodules appearing as an air halo, copper particle deposition, and positive CK7 expression of intermediate liver cells are morphological characteristics indicative of biliary cirrhosis, and all patients had these findings. In previous research, these findings have been reported to be consistent with histological changes in the liver of adult patients with PFIC3 ( 20 ). Furthermore, liver biopsies revealed ductular proliferation with mild inflammation, which is indicative of early stages of fibrosis in the portal tract.…”
Section: Discussionsupporting
confidence: 87%
“…Cholecystolithiasis is a multifactorial disease, the pathogenesis involves both genetic and environmental factors, of these, genetic factors account on an average for 25–29% of the risk (Nakeeb et al, 2002; Stokes et al, 2011 ; 2014). The nuclear gene ABCB4 (ATP-binding cassette B4) is closely related to the occurrence of cholecystolithiasis ( Jirsa et al, 2014 ; Elderman et al, 2015 ). In addition, the variants of ABCG8 and UGT1A1 have been identified to be involved, it may contribute to 21.2% the male population ( Buch et al, 2010 ; Buch et al, 2010 ).…”
Section: Disccusionmentioning
confidence: 99%